Zoonotic Hepatitis E Virus: An Ignored Risk for Public Health - Nan, Yuchen; Wu, Chunyan; Zhao, Qin; Zhou, En-Min (Frontiers in Microbiology, 2017)
Hepatitis E virus (HEV) is a quasi-enveloped, single-stranded positive-sense RNA virus. HEV belongs to the family Hepeviridae, a family comprised of highly diverse viruses originating from various species. Since confirmation of HEV’s zoonosis, HEV-induced hepatitis has been a public health concern both for developing and developed countries. Meanwhile, the demonstration of a broad host range for zoonotic HEV suggests the existence of a variety of transmission routes that could lead to human infection. Moreover, anti-HEV antibody serosurveillance worldwide demonstrates a higher than expected HEV prevalence rate that conflicts with the rarity and sporadic nature of reported acute hepatitis E cases. In recent years, chronic HEV infection, HEV-related acute hepatic failure, and extrahepatic manifestations caused by HEV infection have been frequently reported. These observations suggest a significant underestimation of the number and complexity of transmission routes previously predicted to cause HEV-related disease, with special emphasis on zoonotic HEV as a public health concern. Significant research has revealed details regarding the virology and infectivity of zoonotic HEV in both humans and animals. In this review, the discovery of HEV zoonosis, recent progress in our understanding of the zoonotic HEV host range, and classification of diverse HEV or HEV-like isolates from various hosts are reviewed in a historic context. Ultimately, this review focuses on current understanding of viral pathogenesis and cross-species transmission of zoonotic HEV. Moreover, host factors and viral determinants influencing HEV host tropism are discussed to provide new insights into HEV transmission and prevalence mechanisms.